Automatic identification and analysis of cells using digital holographic microscopy and Sobel segmentation - Xiong, Zihan; Yu, Lan; An, Sha; Zheng, Juanjuan; Ma, Ying; Micó, Vicente; Gao, Peng (Frontiers in Photonics, 2024)
Counting and analyzing of blood cells, as well as their subcellular structures, are indispensable for understanding biological processes, studying cell functions, and diagnosing diseases. In this paper, we combine digital holographic microscopy with cell segmentation guided by the Sobel operator using Dice coefficients for automatic threshold selection and aimed to automatic counting and analysis of blood cells in flow and different kinds of cells in the static state. We demonstrate the proposed method with automatic counting and analyzing rat blood cells (RBCs) flowing in a microfluidic device, extracting quickly and accurately the size, concentration, and dry mass of the sample in a label-free manner. The proposed technique was also demonstrated for automatic segmentation of different cell types, such as COS7 and Siha. This method can help us in blood inspection, providing pathological information in disease diagnosis and treatment.